2006
DOI: 10.1111/j.1745-7262.2006.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with intracavernosal injections in diabetic men with erectile dysfunction

Abstract: Treatment with self-injections of vasoactive drugs in diabetic men with severe ED is a safe and effective alternative in the long term. Diabetic men of both types show the same preferences in quality and quantity of treatment after 10 years. The key point for maintenance in treatment is the adjustment of the therapeutic method and dosage to optimal levels for satisfactory erections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…A recent study by Perimenis et al showed that the long-term self-injection of vasoactive drugs is a highly effective and safe treatment for ED in men with diabetics [53].…”
Section: Erectile Dysfunction Secondary To Diabetesmentioning
confidence: 99%
“…A recent study by Perimenis et al showed that the long-term self-injection of vasoactive drugs is a highly effective and safe treatment for ED in men with diabetics [53].…”
Section: Erectile Dysfunction Secondary To Diabetesmentioning
confidence: 99%
“…Interestingly, insulin dependent diabetics progressed more quickly to the final standardization treatment than non-insulin dependent diabetics, possibly owing to their familiarity with self-injections and willingness to utilize intracavernosal injection therapy. Also, during the 10-year follow-up of intracavernosal injection therapy, both types of diabetics required larger doses of medications and multidrug therapy to achieve satisfactory erections [67]. Current recommendations for intracavernosal injections are an initial trial of alprostadil monotherapy, if this fails or pain at the injection site limits patient satisfaction, a trial of a combination of papaverine/phentolamine or a combination of all three agents should be tried in an effort to reduce the individual dosage and minimize adverse effects [65].…”
Section: Intracavernosal Injectionmentioning
confidence: 99%
“…Diabetes mellitus has been noted to negatively impact the response to intracorporeal injection and is associated with low PSV and poor penile axial rigidity [18]. In a 10-year follow-up study, diabetic patients using self-injection to treat ED had the tendency to switch from a single vasodilator to a combination of vasodilators in order to reach maximal cavernous smooth muscle relaxation and a better erection response [19]. In a recent prospective morphometric study, severe vascular lesions with reduction of cavernous smooth muscle (< 35%) were observed in sildenafil non-responders [20].…”
Section: Tel: +86-21-5492-2824; Fax: +86-21-5492-2825; Shanghai Chinamentioning
confidence: 99%